2010
DOI: 10.1111/j.1744-7917.2010.01327.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of gut‐associated and nest‐associated microbial communities of a fungus‐growing termite (Odontotermes yunnanensis)

Abstract: The digestion of cellulose by fungus‐growing termites involves a complex of different organisms, such as the termites themselves, fungi and bacteria. To further investigate the symbiotic relationships of fungus‐growing termites, the microbial communities of the termite gut and fungus combs of Odontotermes yunnanensis were examined. The major fungus species was identified as Termitomyces sp. To compare the micro‐organism diversity between the digestive tract of termites and fungus combs, four polymerase chain r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 46 publications
(62 reference statements)
2
40
0
Order By: Relevance
“…Therefore Kellner et al [80] believe that Lactobacillus may serve an important role as defense pathogens in the M. smithii system. In another study involving termites, Lactobacillus was found in the insect feces where, in addition to this protection function, it can also serve as a substrate or fertilizer [82, 83]. …”
Section: Discussionmentioning
confidence: 99%
“…Therefore Kellner et al [80] believe that Lactobacillus may serve an important role as defense pathogens in the M. smithii system. In another study involving termites, Lactobacillus was found in the insect feces where, in addition to this protection function, it can also serve as a substrate or fertilizer [82, 83]. …”
Section: Discussionmentioning
confidence: 99%
“…Chlorobacteria and Nitrospirae were also reported to be the dominant bacteria in activated sludge in wastewater treatment, which can degrade ammonia-nitrogen and organic chlorides [3436]. Acidobacteria plays an important role in maintaining the pH value [37,38] and influences metal uptake activity [39,40]. Bacteroidetes is important for degrading cellulose and chitin [4144].…”
Section: Discussionmentioning
confidence: 99%
“…Termites not only attack living trees, but also degrade wood and other celluloses in the terrestrial environment (Long et al 2010). In fact, they can damage many other kinds of materials, from paper materials such as paper, fabrics, and wood structures to noncellulose materials such as asphalt, asbestos, bitumen, lead, and metal foils (Bultman et al 1979).…”
mentioning
confidence: 98%